Gambaran Perawatan Diri Pasien Diabetes Melitus Di Poliklinik Penyakit Dalam Murni Teguh Memorial Hospital - Purba, Valentina; Banjarnahor, Seriga (Universitas Murni Teguh, 2025)
Patients with diabetes mellitus require effective control of blood sugar levels to preventcomplications. Effective control of diabetes mellitus depends on self-care, namely diet,physical exercise, glucose level checks, medication, and foot care. The objective of thisstudy is to determine the description of diabetes mellitus patient self-care. This study is adescriptive study. The research was conducted at the Interna Medicine Polyclinic, MurniTeguh Memorial Hospital. The total population was 140 people and the sample wasobtained as many as 58 people. The data used are primary data and secondary data. Theanalysis was carried out by univariate which is presented in the frequency distribution table.The results of this study indicate that the self-care of diabetes mellitus patients at the InternaMedicine Polyclinic, Murni Teguh Memorial Hospital which includes dietary regulation,physical exercise (exercise), blood sugar level examination, drug use (medication), and footcare, are mostly already used. good (53.4%), but there were still patients with poor self-care(46.6%). It is concluded that the self-care of diabetes mellitus patients is good, but there arestill many who treat themselves poorly. It is recommended that nurses from the InternaMedicine Polyclinic, Murni Teguh Memorial Hospital provide counseling or health educationto visiting patients about self-care including dietary management, physical exercise(exercise), checking blood sugar levels, drug use (medication), and foot care